Enhanced Therapeutic Potential of Hypericum perforatum L.: A Comprehensive In Vitro and In Vivo Evaluation of Nanoparticle-Hydrogel Formulations - Ahmet Arif Kurt; Bashar Ibrahim; Harun Cinar; Ozlem Ozmen (Journal of Nanotechnology)
Nanoparticle (NP)-based hydrogel formulations incorporating natural extracts hold significant promise for advanced drug delivery due to their controlled release profiles and enhanced bioavailability. In this study, both in vitro and in vivo evaluations were conducted on NP hydrogel formulations containing Hypericum perforatum macerate (HPM) extracted with Nigella sativa oil (NSO) and olive oil (OO). poly(lactic-co-glycolic acid) (PLGA) and polylactic acid (PLA)-based NPs were synthesized using the emulsion diffusion–solvent evaporation technique. The formulations were characterized for their morphological, chemical, and bioavailability-related properties. Additionally, their antibacterial efficacy and wound healing potential were assessed. Among the tested formulations, NP-NSO/HPM exhibited the most favorable characteristics, with a particle size of 221.50 ± 4.17 nm, a polydispersity index of 0.334 ± 0.005, and a zeta potential of −28.7 ± 4.35 mV. The hypericin content in the NP-NSO/HPM was determined to be 0.487%, and the cumulative drug release was 94.22% over 80 h, following Higuchi release kinetics. Hydrogels were prepared by physically mixing Carbopol 934 with Aloe vera powder to form a stable network. The NP hydrogels demonstrated significantly higher antibacterial activity against Escherichia coli and Staphylococcus aureus compared to other formulations (p<0.01). In vivo wound healing experiments were performed using 78 male New Zealand rabbits, revealing enhanced wound closure rates and improved histological healing parameters in the NP-treated groups. The HPM-NP hydrogel formulations exhibited substantial potential for wound healing and antibacterial therapy, supporting their further development as promising candidates for the treatment of skin infections and tissue regeneration in clinical settings.